ANALISIS LEAN SERVICE GUNA MENGURANGI WASTE YANG TERJADI PADA PROSES OUT GOING JALUR UDARA DI PT. CITRA VAN TITIPAN KILAT (TIKI) CATAMA JOGJA - Novya Isro' Imah; Fatma Hermining Astuti (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
PT. Citra Van Titipan Kilat (TIKI) Catama Jogja is a service company of shipping goods. TIKI applies the principle that the company's success is measured by the perfection of serving customers and the level of Service Level Agreement it has. The problem in this company is the SLA value that is owned is 77.29%, not in accordance with the company's target of 90-95%. This research was conducted to determine what kind of waste is happening, why waste can occur, and how to reduce waste during the service process. The method used in this study is lean service, which is a work methodology that is applied in service companies in order to produce value according to the wishes of consumers by eliminating existing waste. The tools used are VSMS and VALSAT. Selected tools based on VALSAT calculations are PAM and SCRM. Waste that has been identified were waiting, transportation, error, overprocessing, and movement. The proposed improvement plan by reducing the waste that occurs gives the result that the required processing time has decreased by 14.48% or initially 794 sec to 679 sec.